3‐D Interdigitated electrodes for uniform stimulation of electro‐responsive hydrogels for biomedical applications. Issue 21 (27th August 2013) - Jackson, Nathan; Cordero, Nicolas; Stam, Frank
ABSTRACT Stimuli‐responsive hydrogels are continuing to increase in demand in biomedical applications. Occluding a blood vessel is one possible application which is ideal for a hydrogel because of their ability to expand in a fluid environment. However, typically stimuli‐responsive hydrogels focus on bending instead of radial uniform expansion, which is required for an occlusion application. This article focuses on using an interdigitated electrode device to stimulate an electro‐responsive hydrogel in order to demonstrate a uniform swelling/deswelling of the hydrogel. A Pluronic‐bismethacrylate (PF127‐BMA) hydrogel modified with hydrolyzed methacrylic acid, in order to make it electrically responsive, is used in this article. An interdigitated electrode device was manufactured containing Platinum electrodes. The results in this paper show that the electrically biased hydrogels deswelled 230% more than the non‐biased samples on average. The hydrogels deswelled uniformly and showed no visual deformations due to the electrical bias. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1523–1528